Green Synthesis, Characterization, and Biological Activity of 4-Aminoquinoline Derivatives: Exploring Antibacterial Efficacy, MRSA Inhibition, and PBP2a Docking Insights - Lo’ay A. Al-Momani; Ula A. Abu Shawar; Ayman H. Abu Sarhan; Rand Shahin; Panayiotis A. Koutentis; Mohammad K. Abu-Sini; Nada J. Mohammad (Chemistry, 2025)
A series of 4-aminoquinoline derivatives were prepared using a microwave-assisted method. The reactions were initially carried out on a small scale and subsequently scaled up using a sealed tube. Heating the reactions to 90–150 °C for 90–120 minutes obtained products with up to 95% yields. Structural analysis and characterization were achieved using FT-IR, 1H- and 13C-NMR spectroscopy and HR-MS. Four compounds displayed low-to-moderate antibacterial activity, with 6-chlorocyclopentaquinolinamine (7b) exhibiting potent inhibition against MRSA (MIC = 0.125 mM) and 2-fluorocycloheptaquinolinamine (9d) showing activity against S. pyogenes (MIC = 0.25 mM). Structure–activity relationship (SAR) docking studies within the Penicillin Binding Protein (PBP2a) binding site (PDB: 4DK1) showed that compounds 7b and 5b (7-chlorophenylquinolinamine) bind through hydrophobic interactions (ALA601, ILE614), hydrogen bonding (GLN521), and halogen contacts (TYR519, THR399). Compound 7b demonstrated enhanced MRSA inhibition due to additional π-alkyl interactions and optimal docking parameters. Conversely, the bulky structure of 9d may explain its weaker activity as it likely hindered binding to the target site. This paper highlights the role of structural features in antibacterial efficacy and guides the future optimization of 4-aminoquinoline derivatives.